2019
DOI: 10.3390/ijms20246361
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Enhances α1-Adrenergic Vasoconstriction via S1P2–G12/13–ROCK Mediated Signaling

Abstract: Sphingosine-1-phosphate (S1P) has been implicated recently in the physiology and pathology of the cardiovascular system including regulation of vascular tone. Pilot experiments showed that the vasoconstrictor effect of S1P was enhanced markedly in the presence of phenylephrine (PE). Based on this observation, we hypothesized that S1P might modulate α1-adrenergic vasoactivity. In murine aortas, a 20-minute exposure to S1P but not to its vehicle increased the Emax and decreased the EC50 of PE-induced contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…However, a few studies provide evidence that S1P 2 or S1P 3 might play a role in the regulation of heart function. In a recent study, we reported a dominant role of S1P 2 in S1P-induced enhancement of vasoconstrictor stimuli in the circulation [54]. Therefore, in the present study we aimed to characterize the role of these two receptors in mediating CF reduction by S1P.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, a few studies provide evidence that S1P 2 or S1P 3 might play a role in the regulation of heart function. In a recent study, we reported a dominant role of S1P 2 in S1P-induced enhancement of vasoconstrictor stimuli in the circulation [54]. Therefore, in the present study we aimed to characterize the role of these two receptors in mediating CF reduction by S1P.…”
Section: Discussionmentioning
confidence: 89%
“…However, this putative mechanism requires further investigation. Moreover, S1P 2 activation might also sensitize the smooth muscle to other vasoconstrictor stimuli, as has been shown in the systemic circulation [54]. S1P is frequently implicated in cardioprotection [21,22,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…These collective observations suggest that the α2-adrenergic stimulation of adipocytes induces the extracellular release of LPA, resulting, in turn, in the regulation of preadipocyte growth [ 44 ]. Quite interestingly, among these PGs, α-adrenergic, and ROCK signaling mechanisms, it has also been shown that PGF2α-related signaling is closely linked to the Ga12-ROCK signaling pathway [ 45 , 46 ], and α1-adrenergic vasoconstriction is linked with S1P2–G12/13–ROCK-mediated signaling [ 47 ]. However, our previous study indicated that the inhibition of ROCKs by pan-ROCK-is, Rip, or Y27632 additively, but not synergistically, affected the effects that are induced by PGs on DIF+ [ 22 , 48 ], suggesting that both types of signaling may be independent in terms of the DIF+ in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…S1P may cause the relaxation of vascular smooth muscle since endothelial cell nitric oxide synthase (eNOS) is activated in the endothelium through the PI3K/Akt process, which occurs downstream of the S1P 1-3 /G i signal pathways. However, since the signal transduction pathway of S1P (S1P 2 and S1P 3 ) is involved in PLC/IP 3 and Rho/Rho-kinase, which are related to Ca 2+ dynamics and Ca 2+ sensitization, respectively, S1P can generate tension in vascular smooth muscle with Ca 2+ signal pathways similar to trachea [12,107]. Previous reports have demonstrated that S1P causes contraction in coronary artery with an increase in intracellular concentration of Ca 2+ (Ca 2+ dynamics) and Rho-kinase activation (Ca 2+ sensitization) [108] (Figure 5), and that S1P also causes contraction in the aorta with an increase in the intracellular Ca 2+ concentration through SOCE [109] (Figure 5).…”
Section: Effects Of Smooth Musclementioning
confidence: 99%